Toppling of rigid electric equipment during earthquakes. (1st August 2018) - Jaimes, Miguel A.; Candia, Gabriel
Highlights: This study presents a framework for seismic toppling risk of rigid equipment. Three support conditions are studied: simply supported, anchored, base isolated. Anchored and simply supported equipment performed well in near source conditions. Reliability index increases almost linearly with the block's aspect ratio. Abstract: This study presents a general formulation for toppling risk assessment of rigid electrical equipment during earthquakes. The seismic response, toppling fragility functions and toppling risk were examined for three types of support conditions, namely: (1) equipment simply supported on the foundation; (2) equipment anchored to the foundation; and (3) equipment supported on a seismic base isolator. Because empirical fragility functions for overturning equipment remain insufficient, the present study relies on numerical analysis and a solid physical background to compute risk. These results should aid designers in the selection of appropriate support conditions or mitigation measures for rigid electric equipment in seismic prone regions. As an example, the toppling risk methodology is presented using Mexican seismicity and a set of nine electrical equipment commonly used throughout Mexican power stations, with heights between 3 and 5 m, covering an ample range of frequency parameters (1.54 <  p < 2.16 rad/s), and block dimensions (1.58 m <  R < 2.49 m). Further, the effects of site-to-source distance for sites located on firm soil are studied in detail, as the frequency content of these ground motions differ significantly and play a key role in the toppling vulnerability of the blocks. The study shows that the reliability index increases monotonically with increasing block aspect ratio and block size for the nine equipment and the three support conditions studied. This investigation also demonstrates that the reliability of free-standing equipment due to near-source ground motions is slightly higher than that of anchored equipment or base isolated equipment. In contrast, for far-field ground motions, the reliability for anchored equipment is slightly higher than that of free-standing or base isolated equipment.